A study assessing the feasibility of randomization of pediatric and young adult patients between matched unrelated donor bone marrow transplantation and immune‐suppressive therapy for newly diagnosed severe aplastic anemia: A joint pilot trial of the North American Pediatric Aplastic Anemia Consortium and the Pediatric Transplantation and Cellular Therapy Consortium. Issue 10 (9th August 2020) - Pulsipher, Michael A.; Lehmann, Leslie E.; Bertuch, Alison A.; Sasa, Ghadir; Olson, Timothy; Nakano, Taizo; Gilio, Alfred; Burroughs, Lauri M.; Lipton, Jeffrey M.; Huang, James N.; Dickerson, Kathryn E.; Bertaina, Alice; et al.
Abstract: Background: Recent data show survival after matched unrelated donor (MUD) bone marrow transplantation (BMT) is similar to matched sibling procedures for young patients with severe aplastic anemia (SAA). Donor delays, risk of transplant‐related mortality (TRM), and concern about chronic graft versus host disease raise questions about whether MUD BMT or immune suppression therapy (IST) should be preferred initial therapy for young patients lacking matched sibling donors. Procedure: We performed a pilot trial to assess the feasibility of randomizing patients under age 26 with newly diagnosed SAA to receive IST versus MUD BMT. Primary aims assessed the acceptability of randomization and timing of BMT. Secondary aims measured toxicities, response, and survival. Results: Sixty‐seven patients with possible SAA were screened at nine centers. Of 57 with confirmed SAA, 23 underwent randomization and received therapy with a median follow‐up of 18 months. Of 12 randomized to BMT, 10 started BMT as initial therapy at a median of 36 days after randomization. One BMT recipient experienced secondary graft failure, requiring a second procedure. Six of 11 randomized to IST responded, whereas five with refractory disease underwent successful salvage BMT. One patient achieving complete response relapsed after discontinuation of immune suppression and died of infection after salvage BMT. Conclusions: This feasibility study showed that a high percentage of patients underwent randomization and received up‐front MUD BMT. Our study lays the groundwork for a larger randomized trial that will define best initial therapy for young patients with SAA who have an available MUD.